Moderating Role of Education and Gender on the Effects of Celebrity Endorsement on Strength, Uniqueness, and Favourability in Brand Association: Evidence from India. (December 2020) - Saini, Aarti; Parayitam, Satyanarayana
Volumes of research documented the positive effects of celebrity endorsement in influencing the consumers in their purchase decisions. One area that has been understudied, to our knowledge, is the effect of level of education and gender on celebrity endorsement. The present study considers level of education as a moderator in the relationship between the effect of celebrity endorsement and its outcomes. In addition, we also study gender as a moderator in the relationship between trustworthiness and favourability. Using a structured instrument, data were collected from 678 respondents in a cosmopolitan city in northern part of India and analysed after checking the psychometric properties of the instrument. A conceptual model was developed and evaluated using hierarchical regression. Results showed that level of education plays a major role in changing the strength of relationship between perceived characteristics of celebrities and customer-based brand equity in terms of strength, uniqueness, and favourability of brand association. Results reveal that consumers with lower levels of education are more likely to get influenced by characteristics of celebrities when compared to consumers with higher levels of education. Apart from education, gender also plays a crucial role as a moderator in the relationship between trustworthiness and favourability. The implications are discussed.